Herbal medicine in chronic wounds in Calabria region of Italy: an ethnographic study - Costa, Davide; Serra, Raffaele (Frontiers in Sociology, 2025)
IntroductionTraditional herbal medicine remains a vital, though often overlooked, component of chronic wound management in rural and underserved areas of southern Italy. In Calabria, this enduring practice reflects both cultural continuity and systemic healthcare gaps.MethodsAn ethnographic study was conducted involving 120 patients attending a vascular surgery clinic in Catanzaro, Calabria. Data were collected through semi-structured interviews, participant observation, and field notes, focusing on the use and transmission of herbal remedies for chronic ulcers.ResultsThe findings reveal that older women, particularly grandmothers and mothers, are the primary custodians of local ethnomedical knowledge. Remedies such as Achillea millefolium poultices and Citrus bergamia decoctions are employed to treat various types of chronic wounds, including venous, arterial, and diabetic ulcers. These treatments are adapted to a vernacular taxonomy of wound severity and are often accompanied by symbolic or ritual meanings. Despite biomedical availability, patients—especially those from low-income or rural settings—continue to use plant-based therapies due to limited healthcare access, long waiting lists, and a perceived over-medicalization of care. Gender dynamics were evident, with women maintaining knowledge transmission within the household and men engaging more in self-treatment related to occupational injuries.DiscussionIn this Calabrian context, herbal medicine functions not as an alternative, but as a parallel and coexisting system of care. It offers cultural affirmation, therapeutic autonomy, and practical solutions amid healthcare challenges. Documenting such practices deepens our understanding of medical pluralism and highlights the need to integrate local voices into ethnobotanical research.